2016
DOI: 10.1080/15389588.2016.1144878
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of off-the-system traffic crashes in Miami–Dade County, Florida, during 2005–2010

Abstract: This understanding of patterns can help the county target high-risk areas and help to reduce crash fatalities to create a safer environment for motorists and pedestrians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The pattern of distribution was considered to be clustered if the value of Moran’s I was > 0 and P < 0.05; otherwise, the pattern was considered to be nonclustered [ 18 ]). Local spatial autocorrelation and the Getis-Ord Gi* statistic were used to identify the hot spots of CHD birth prevalence within the study area (the Gi* statistics is actually a Z score, and Z score values equal or greater than 1.96 were used to indicate the significance of observed hot spots with a P value of less than 0.05) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pattern of distribution was considered to be clustered if the value of Moran’s I was > 0 and P < 0.05; otherwise, the pattern was considered to be nonclustered [ 18 ]). Local spatial autocorrelation and the Getis-Ord Gi* statistic were used to identify the hot spots of CHD birth prevalence within the study area (the Gi* statistics is actually a Z score, and Z score values equal or greater than 1.96 were used to indicate the significance of observed hot spots with a P value of less than 0.05) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have been many studies of crashes undertaken internationally using techniques such as the Moran's I statistic, the Getis-Ord Gi* statistic and KDE individually and in combination. In some studies the crashes were spatially and/or temporally partitioned (Chance Scott et al, 2016;Prasannakumar et al, 2011). Some studies used severity indices, as well as actual counts, with more severe crashes being given a higher weighting (Choudhary, Ohri & Kumar, 2015;Soltani & Askari, 2017).…”
Section: Findings From Previous Studies Using Spatial Analysismentioning
confidence: 99%
“…Some studies used severity indices, as well as actual counts, with more severe crashes being given a higher weighting (Choudhary, Ohri & Kumar, 2015;Soltani & Askari, 2017). The results of the studies showed significant clustering of crashes, especially on arterial roads and near urban activity centres, but found that in certain locations the distribution of crashes was random (Chance Scott, Sen Roy & Prasad, 2016;Prasannakumar et al, 2011;Soltani & Askari, 2017). Benedek, Ciobanu and Man (2016) used network-based analysis to identify crash hot spots and found that the number of crashes was directly proportional to the traffic volume, and that the hot spots were in locations where traffic was high.…”
Section: Findings From Previous Studies Using Spatial Analysismentioning
confidence: 99%
“…In traffic crash analysis, many empirical findings indicate that the spatial pattern of traffic collisions can vary according to a wide range of factors. The distribution of hot spots or hot zones can, for example, vary based on temporal change [20], road types (e.g., highways and urban roads) [21], land uses [13] and pedestrians or other vulnerable groups [22]. Putting the spatial context into the perspectives of hotspot and hot zone identification is therefore conducive to formulating geographical-specific and effective road safety measures.…”
Section: Literature Reviewmentioning
confidence: 99%